PENGARUH MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, EXTENDING (CORE) TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SDN KESAMBI - Sriwigati, Mila; Kurniawan, Machful Indra (Jurnal Pendidikan Dasar Flobamorata, 2024)
In the world of education, it is found that some students experience difficulties in understanding the concept of critical thinking and strategies for applying it in solving various problems. These limitations can affect the cognitive development and analytical skills of students. The research population is 28 students. This research method uses a quantitative experiment, the type of Pre-Experiment research, assisted by SPSS 26 software. The results show that to test the hypothesis and answer the problem formulation, the data analysis technique uses a paired t-test. This can be seen from the average value when given the P treatment Connecting, Organizing, Reflecting, Extending (CORE) Learning Model Against Students' Critical Thinking Ability in Pancasila Education Subject at SDN Kesambi. After testing the hypothesis using the Paired T-Test t test, the average pretest data is smaller than the average posttest data. Sig value is obtained. (2-tailed) is less than 0.05 and the eta value is more than 0.14 meaning that there is an effect of using the Connecting, Organizing, Reflecting, Extending (CORE) Learning Model on Students' Critical Thinking Ability in Pancasila Education Subjects at SDN Kesambi Meaning there is an increase in student learning outcomes after applying the use of the Connecting, Organizing, Reflecting, Extending (CORE) Learning Model Effect on Students' Critical Thinking Ability in Pancasila Education Subjects at SDN Kesambi